P15 Non-invasive assessment of hepatic fibrosis in prior non-responders to hepatitis C virus treatment—a comparison of eight marker panels of liver fibrosis. (16th November 2010) - Tanwar, S; Ellis, E; Herold, C; Rosenberg, W
Abstract : Introduction: The detection of advancing fibrosis in patients who have previously failed standard therapy for hepatitis C virus (HCV) is important both for ascertaining prognosis and stratifying patients for further treatment with emerging therapies. Whilst liver biopsy remains the reference standard, non-invasive markers of liver fibrosis may be able to reduce the need for liver biopsy in this group of patients. Method: 80 previous non-responders to pegylated interferon and ribavirin (46 male, 34 female, age 24–98 years, mean 48.9) were recruited from five centres. Serum was taken at the time of liver biopsy. Seven tests of liver fibrosis and simple biochemical markers were compared. These were: Hyaluronic acid (HA); Indirect tests: APRI, Forn's, Fib-4; Tests including HA: SHASTA, Hepascore, Fibrometer and ELF test. Area under receiver operating characteristic curves (AUROC) were plotted for minimal fibrosis (F0–1 vs F2–6), mild fibrosis (F0–2 vs F3–6), moderate fibrosis (F0–3 vs F4–6), and severe fibrosis/cirrhosis (F0–4 vs F5–6). Results: AUROCs (and asymptotic 95% confidence intervals) are presented for each test for minimal, mild and severe fibrosis. Abstract P15 Table 1 Results Test F0–1 vs F2–6 n=26 n=54 F0–2 vs F3–6 n=35 n=45 F0–4 vs F5–6 n=57 n=23 ELF 0.8020.705–0.900 0.8510.770–0.932 0.8590.765–0.953 Hepascore 0.7770.674–0.880 0.7570.653–0.861 0.8590.766–0.925 Fibrometer 0.7750.669–0.876 0.7400.632–0.849 0.8080.698–0.917 SHASTA 0.6520.532–0.772 0.6540.535–0.773 0.8060.691–0.921 HA 0.6680.551–0.785 0.7100.597–0.822 0.7690.637–0.902 FIB-4 0.7140.597–0.832 0.7680.666–0.869 0.8140.704–0.924 Forns 0.7170.597–0.837 0.7630.660–0.866 0.8130.701–0.925 APRI 0.6540.529–0.780 0.6740.557–0.791 0.7640.650–0.878 ELF was best at detecting lesser degrees of fibrosis and was better than the indirect marker panels either with or without HA. ELF and Hepascore were best at detecting advanced fibrosis, but other panels performed adequately with similar AUCs. Conclusion: In this cohort of previous non-responders to HCV treatment, the ability to discriminate advanced fibrosis appears to be similar amongst most of the markers tested. In contrast, of the eight markers tested in this study, the ELF panel appears to have the most consistent diagnostic performance across all stages of fibrosis and performs well in the detection of minimal and mild fibrosis. ELF testing would permit stratification of previous non-responders for further anti-HCV and anti-fibrotic therapy and for screening for complications of cirrhosis.